ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI LAMPUNG - sophan sophan; megasari megasari; Heri Kurniansyah; Jamal Muhammad Nasir (Universitas Mitra Indonesia, 2022)
ABSTRACTThis test aims to examine the effect of human resources on the quality of information on the provision of government financial statements. The influence of information technology on the quality of information on the provision of government financial statements. The effect of internal control on the quality of information on the provision of government financial statements. The effect of accounting understanding on the quality of information on the provision of government financial statements. External influence on the quality of information on the provision of government financial statements.The population in this study were some of the employees of the Lampung provincial government financial and development supervisory agency. Sample selection by purposive sampling. With a total of 40 respondents. The data used in this study are primary data. Data collection techniques by distributing questionnaires to financial and auditors. Technical analysis of data using multiple linear regression test.The results of this study found that human resources have a positive and partially significant effect on the quality of information on government financial statements. Information technology has a positive and significant effect on the quality of government financial statement information. Internal control has a positive and significant effect on the quality of government financial statement information. The level of understanding of accounting has a positive and significant effect on the quality of information on government financial statements. External factors have a positive and significant effect on the quality of government financial statement information.Keywords :Utilization of human resources information technology, internal control systems, accounting understanding, external factors, the quality of information on the financial statements of the Lampung provincial government.